Rancang Bangun Perangkat Lunak Komunikasi Radio Adeunis Radio Frequency (ARF)7429B pada Sistem Radar Sekunder - Utama, Zaini Agung; Darjat, Darjat; Hidayatno, Achmad (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Adeunis Radio Frequency (ARF)7429B is a hardware module which will be used for the application of radio communication in secondary radar system. ARF module has AT Command and Register which can be accessed by using a software. This research is a designing and making to integrate between ARF hardware and MATLAB software. The accessing process of ARF itself is in two ways through Universal Serial Bus (USB) computer. ARF module has frequency between 902-928 MHz which is divided into 50 channels. The exchanging process of information between ARFs happens without cable (wireless) using Frequency Shift Keying (FSK) modulation. The AT command can be accessed only by using software in microcontroller or computer. The command given in this communication is appropriated with the character of AT command itself, therefore the accessing process can be happened. The data input and output received in ARF communication is ASCII character. In transmitting process of information. The data is carried in channels randomly by using Frequency Hopping Spread Spectrum (FHSS) method. Keyword : Adeunis Radio frequency (ARF)7429B, MATLAB, Secondary Radar, Receiving and Transmitting Data.